An Analysis of Illocutionary Acts in Fast and Furious 6 Movie - I Kadek Rio Sandika Putra; Ida Ayu Putri Gita Ardiantari (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study aims to identify the types of illocutionary acts and to analyze the implied meanings contained within them in Fast and Furious 6 movie. The analysis is grounded in Searle’s (1979) theory of illocutionary acts to categorize the utterances, while Leech’s (1981) semantic theory, specifically the concept of connotative meaning, is applied to interpret the implied meanings. The data were collected using a note-taking technique, focusing on dialogues that contain potential illocutionary acts. A qualitative method was employed to analyze the data, allowing for in-depth interpretation of language functions and underlying meanings. The findings reveal that all five types of illocutionary acts representatives, directives, commissive, expressive, and declaratives are present in the movie. However, commissive and directives emerge as the most dominant types, indicating that the characters frequently express commitments or intentions regarding future actions and attempt to influence the hearers to perform certain acts.